BASKETBALL COACHES’ FEEDBACK: THE SCIENCE AND ART BEHIND - Rovira, Mar (Sport- és Egészségtudományi füzetek, 2025)
Mar Rovira gave a theoretical introduction to giving feed-back and the fundamentals of operant conditioning, a learn-ing methodology. In the second part, she conducted an ex-ercise with conference attendees to help them implement it in practice. Coaches are teachers who must teach skills, strategies and behaviors by providing the best possible feedback. Positive reinforcement: If we add something useful or pleasant the Player will repeat it again. Every time the Play-er does a good defense, a good effort, the trainer reinforces/ rewards him by clapping, cheering or with simple phrases such as ‘very good’, ‘well done’, ‘bravo’. This is a simple and cheap tool for creating a powerful, empowering and honest environment.